Role of Peer Support in Enhancing Students’ Speaking Skills at Universitas Pattimura - Dian Ayu; Sultan Baa; Baso Jabu (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study aims to investigate how peer support facilitates the teaching and learning process of speaking among English as a Foreign Language (EFL) students at Pattimura University. The background of this research is rooted in common challenges encountered by EFL learners, particularly difficulties in developing speaking skills due to anxiety, low self-confidence, limited vocabulary, and insufficient opportunities for authentic communication in English. These challenges often hinder students’ active participation in speaking activities. Therefore, peer support is considered a promising instructional approach that emphasises collaboration, mutual assistance, and horizontal interaction among students, creating a supportive and less intimidating learning environment. This study employs a descriptive qualitative research design to obtain an in-depth understanding of how peer support is implemented, how students perceive its impact, and what challenges arise during its application in speaking instruction. The participants of this study were students from the English Education Study Program at Pattimura University who actively engaged in peer-support-based speaking activities. Data were collected through classroom observations, semi-structured interviews, and document analysis. The collected data were then analysed using the stages of data reduction, data display, and conclusion drawing as proposed by Miles and Huberman to ensure systematic and meaningful interpretation. The findings reveal that peer support was implemented through various strategies, including peer tutoring, cooperative learning, and peer feedback. These approaches were found to be effective in increasing students’ active participation, reducing anxiety when speaking, and fostering greater learner autonomy. Students reported that learning with peers helped them feel more confident, motivated, and comfortable expressing ideas in English. Additionally, peer interaction encouraged constructive feedback and collaborative problem-solving. However, several challenges were identified, such as differences in language proficiency among students, unequal participation within groups, and limited instructional time. Overall, this study highlights the significant role of peer support in enhancing EFL students’ speaking skills and provides valuable insights for educators in designing more collaborative, inclusive, and student-centred learning environments